Good care practices for people who use drugs in the context of psychosocial care (Research, Society and Development, 2021)
Objective: reflect on good mental health practices in caring for people who use drugs in the context of psychosocial care. Method: reflective theoretical study supported by a narrative review of literature, in the Latin American and Caribbean Literature in Health Sciences and PubMed/Medical Literature Analysis and Retrieval online databases, with the selection criteria: articles in Portuguese, English and Spanish; available in full, which portrayed the theme related to the reflection of good practices in the last twenty years. Results and discussion: to discuss and reflect on good practices in mental health, four thematic categories were created: Access to services and use of the Health Care Network (RAS) by users of Psychoactive Substances; Protagonism and autonomy of the person in mental health care; Humanized care in the territory and harm reduction; and Incorporation of the family into care. Conclusion: despite the advances identified in the perspective of psychosocial care, it is still necessary to demonstrate the importance of community services that serve people who use drugs.